Let's solve the problem step by step in expanded form.
- We start with \( 22 \times 3 \).
- We rewrite 22 as \( 20 + 2 \).
So, we have: \[ (20 + 2) \times 3 \]
-
By using the distributive property, we can expand this: \[ (20 + 2) \times 3 = (20 \times 3) + (2 \times 3) \]
-
Now we calculate \( 20 \times 3 = 60 \) and \( 2 \times 3 = 6 \).
So, we can fill in: \[ (20 + 2) \times 3 = (20 \times 3) + (2 \times 3) = 60 + 6 \]
- Finally, we have to fill in the equations based on the given statements:
- From \( (20 + ?) \times 3 \), we can see that \( ? \) is \( 2 \) since \( 20 + 2 = 22 \).
- The next part, \( (20 \times ?) + (2 \times 3) \) needs \( ? \) which is \( 3 \) since we get \( 20 \times 3 = 60 \).
- The last part \( ? + 6 = 66 \) gives us \( ? = 60 \).
So, filling in the blanks:
- \( (20 + 2) \times 3 \)
- \( (20 \times 3) + (2 \times 3) \)
- \( 60 + 6 = 66 \) (therefore the answer to the last blank is 60).
Thus, the completed equations are: \[ (20 + 2) \times 3 \] \[ (20 \times 3) + (2 \times 3) \] \[ 60 + 6 = 66 \]